Are Bumblebees Relevant Models for Understanding Wild Bee Decline? - Ghisbain, Guillaume (Frontiers in Conservation Science, 2021)
The unsustainable use of ecosystems by human societies has put global biodiversity in peril. Bees are, in this context, a popular example of a highly diversified group of pollinators whose collapse is a major concern given the invaluable ecosystem services they provide. Amongst them, bumblebees (Bombus) have increasingly drawn the attention of scientists due to their dramatic population declines globally. This regression has converted them into popular conservation entities, making them the second most studied group of bees worldwide. However, in addition to have become relevant models in the fields of ecology, evolution and biogeography, bumblebees have also been used as models for studying wild bee decline and conservation worldwide. Integrating evidence from the comparative ecology and resilience of bumblebees and wild bees, I discuss the relevance of using Bombus as radars for wild bee decline worldwide. Responses of bumblebees to environmental changes are generally not comparable with those of wild bees because of their relatively long activity period, their inherent sensitivity to high temperatures, their relatively generalist diet breadth and many aspects arising from their eusocial behavior (e.g. colony homeostasis). Moreover, important differences in the available historical data between bumblebees and other bees make comparisons of conservation status even more arduous. Overall, these results reinforce the need for conservation actions that consider a higher level of understanding of ecological diversity in wild bees, highlight the need for an updated and more extensive sampling of these organisms, and emphasize that more caution is required when extrapolating trends from model species.